Estilos de crianza y condiciones sociodemográficas en padres de niños de segundo grado de primaria, ciudad de Caballococha 2024 - Sampayo Cordero, Jorstin (2025)
The present study was carried out with the objective of determining the relationship between parenting styles and socio-demographic conditions in parents of children in the second grade of primary school, from three public educational institutions in the city of Caballococha, 2024. It was a basic, descriptive correlational, non experimental and cross-sectional design, with a sample of 173 parents. The results showed that there is a significant relationship between parenting styles and socio demographic conditions (p = 0.000). Similarly, there is a significant relationship between parenting styles and the dimensions gender of parents and age range of parents with a value of p = 0.001. The dimensions marital status, birth order of children, parents' educational level and family structure also have a significant relationship with learning styles (p = 0.000). In conclusion, parenting styles in the studied population are conditioned by socio-demographic factors.